SPORTSMEN'S HEALTH AND NUTRITION: A STUDY - Walke, Aruna Babasaheb (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Khiladi is the pride and source of inspiration for any country. His physical and mental health rests on the strong foundation of the country's sporting achievements. Athletes need to be in good health to perform at their best, have a long career and be less prone to injuries. In today's era, not only skill but also health management is important to survive in global level competitions. Proper diet, regular exercise, maintenance of mental health and proper rehabilitation—all these aspects should be included in the health management of athletes. Coordination between the government, sports organizations, coaches and medical experts is also essential to ensure the good health of sportspersons in the country.